2023
DOI: 10.1186/s42408-023-00200-8
|View full text |Cite
|
Sign up to set email alerts
|

Climate influences on future fire severity: a synthesis of climate-fire interactions and impacts on fire regimes, high-severity fire, and forests in the western United States

Abstract: Background Increases in fire activity and changes in fire regimes have been documented in recent decades across the western United States. Climate change is expected to continue to exacerbate impacts to forested ecosystems by increasing the frequency, size, and severity of wildfires across the western United States (US). Warming temperatures and shifting precipitation patterns are altering western landscapes and making them more susceptible to high-severity fire. Increases in large patches of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 133 publications
0
8
0
1
Order By: Relevance
“…Childs et al [18] found that in the last ten years, daily fine particulate matter (PM 2.5 ) concentrations from smoke have risen by up to 5 µg m −3 in the Western US. Abatzoglou et al [19] also found that interannual variations in area burned in the Western US are strongly positively correlated with climactic warming and drying, with large increases in acres burned by wildland fires since 1980, and these trends are expected to continue [20]. Local ozone photochemistry (titration) during smoky conditions in urban environments primarily depends on the amount of available nitrogen oxides (NO x ), as large concentrations of VOCs are typically transported with the smoke plume [21].…”
Section: Introductionmentioning
confidence: 99%
“…Childs et al [18] found that in the last ten years, daily fine particulate matter (PM 2.5 ) concentrations from smoke have risen by up to 5 µg m −3 in the Western US. Abatzoglou et al [19] also found that interannual variations in area burned in the Western US are strongly positively correlated with climactic warming and drying, with large increases in acres burned by wildland fires since 1980, and these trends are expected to continue [20]. Local ozone photochemistry (titration) during smoky conditions in urban environments primarily depends on the amount of available nitrogen oxides (NO x ), as large concentrations of VOCs are typically transported with the smoke plume [21].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is likely to continue to intensify the effects of fire in many forested areas globally, by potentially leading to more frequent, large, and/or severe wildfires (Canadell et al., 2021; Jones et al., 2022; Wasserman & Mueller, 2023). This trend is likely to be paralleled by a rise in the use of prescribed fires in an effort to mitigate the escalating threat to human life and infrastructure posed by these intensified wildfire events (Kolden, 2019; Varner et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…El impacto creciente del cambio climático ha incrementado la frecuencia y severidad de los incendios forestales, lo que representa un riesgo significativo para los ecosistemas y comunidades, haciendo imprescindibles sistemas de detección temprana eficientes (Wasserman & Mueller, 2023). Dichos sistemas son claves para alcanzar unos Objetivos de Desarrollo Sostenible de la ONU, especialmente aquellos enfocados en la acción climática (Carta, Zidda, Putzu, Loru, Anedda & Giusto, 2023;Robinne, 2021).…”
Section: Introductionunclassified